Pch Genes Control Biofilm and Cell Adhesion in a Clinical Serotype O157:H7 Isolate - Andreozzi, Elisa; Gunther, Nereus W.; Reichenberger, Erin R.; Rotundo, Luca; Cottrell, Bryan J.; Nuñez, Alberto; Uhlich, Gaylen A. (Frontiers in Microbiology, 2018)
In a previous study, induction of the Escherichia coli serotype O157:H7 SOS response decreased csgD expression in the clinical isolate PA20 at 30°C but strongly induced genes in the horizontally transferred-DNA regions (HTR), including many known virulence regulators. To determine the role of HTR regulators in the control of csgD and curli, specific regulators were plasmid-expressed in the wild-type and mutant strains of PA20 and its biofilm-forming derivative, 20R2R. At 30°C, plasmid over-expression of the O157:H7 group 3 perC homolog, pchE, strongly repressed PA20 csgD transcription (>7-fold) while the group 1 homologs, pchA and pchB, resulted in smaller reductions (<2.5-fold). However, SOS induction decreased rather than increased pchE expression (>6-fold) making group 1 pch, which are enhanced by the SOS response, the likely SOS-induced csgD repressors. Plasmid-based pchE over-expression also reduced 20R2R biofilm formation (>6-fold) and the curli-dependent, Congo red affinity of both PA20 and 20R2R. However, to properly appreciate the regulatory direction, expression patterns, and environmental consequences of these and other CsgD-controlled functions, a better understanding of natural pchE regulation will be required. The effects of HTR regulators on PA20 and 20R2R adhesion to HEp-2 cell at host temperature were also studied. Under conditions where prophage genes were not induced, curli, rather than espA, contributed to host cell adhesion in strain 20R2R. High levels of pchE expression in trans reduced curli-dependent cell adherence (>2-fold) to both 20R2R and the clinical isolate PA20, providing a host-adapting adhesion control mechanism. Expression of pchE was also repressed by induction of the SOS response at 37°C, providing a mechanism by which curli expression might complement EspA-dependent intimate adhesion initiated by the group1 pch homologs. This study has increased our understanding of the O157 pch genes at both host and environment temperatures, identifying pchE as a strong regulator of csgD and CsgD-dependent properties.